Crystal transition behaviors of CL-20 in polyether solid propellants plasticized by nitrate esters containing both HMX and CL-20. (15th November 2017) - Zhou, Shuiping; Pang, Aimin; Tang, Gen
Abstract : Co-crystal of CL-20/HMX was formed in NEPE propellants with the co-existence of CL-20 and HMX after curing for two weeks. Abstract : Crystal transition behaviors of CL-20 in polyether solid propellants plasticized by nitrate esters (NEPE propellants) in the presence of both HMX and CL-20 at 50 °C were researched by X-ray diffraction, scanning electron microscopy and dynamic mechanical analysis. It was revealed that the crystal transition phenomenon of CL-20 was not noticeable when CL-20 existed alone in the NEPE propellants at 50 °C. When the second explosive was added, the crystal transition behaviors of CL-20 were changed greatly. With the co-existence of HMX and CL-20, the crystal form of CL-20 was changed, and a co-crystal of CL-20/HMX formed in NEPE propellants at 50 °C. The formation mechanism for the CL-20/HMX co-crystal in NEPE propellants was studied by the integration of theory and experimental data.